PAEONIA EMODI ROYLE ATTENUATES ADJUVANT-INDUCED ARTHRITIS THROUGH DOWNREGULATION OF INFLAMMATORY CYTOKINE SIGNALING AND BY REDUCING THE OXIDATIVE STORM - SYED IHTISHAM HAIDER, QAISER JABEEN, IRFANA LALARUKH, MUHAMMAD RAMZAN KALEEM, MUHAMMAD MUZAMMIL RAMZAN, NUMERA ARSHAD, AISHA SHEHZAD, ASIM RAZA, NAMRA ZAREEN, SOHAIB IQBAL, MUHAMMAD AHMED KHAN, IJAZ ALI (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Background: Paeonia emodi Royle is associated with the family Paeoniaceae and has traditionally been used to relieve muscular strains, headaches and rheumatic inflammation by local communities in various countries. Study aims: The current study was set out to look at the therapeutic potential of Paeonia emodi Royle in heat induced pain and adjuvant-induced arthritis paradigm. Methodology: Hot plate and tale immersion methods were used on rats to investigate the analgesic potential of Paeonia emodi Royle. To develop immune-mediated rheumatoid arthritis, the left hind paw of the rat was injected with complete Freund's adjuvant (CFA) and the aqueous methanolic extract of Paeonia emodi Royle (IPE) was given orally for 28 days. The extent of the paw oedema and the arthritic score in the animals were tracked over the course of the experiment. On 28th day, general hematology and blood biochemistry of animals were computed along with systemic inflammatory proteins including C-reactive proteins and rheumatoid factor. Real-time quantitative polymerase chain reaction (qPCR) was utilized to assess the expressions of interleukins (IL-1β and IL-6), tumor necrosis factor (TNF-α), nuclear factor (NF-kB) and cyclooxygenase enzymes (COX-2). PGE2 was quantified in the blood through ELISA test. Results: At two different doses, 500 mg/Kg and 1000 mg/Kg; p.o., IPE exhibited dose-dependent pain-relieving effect in the hot plate test (with highest retention time of 12.55 ± 0.34 & 14.56 ± 0.47 seconds) and tail immersion (response time of 12.55 ± 0.38 & 13.34 ± 0.20 seconds) tests. IPE induced a significant reduction in inflamed paw and arthritic score on 14th day of CFA injection. The extract considerably curtailed the mRNA expression of TNF-α, interleukins, and COX-2 at the doses of 500 mg/Kg; p.o. (p ≤ 0.05) and 1000 mg/Kg; p.o (p ≤ 0.001) respectively. IPE significantly enhanced the antioxidant activities of the both superoxide dismutase (SOD) and catalase (CAT) enzyme along with significantly lowering the levels of TBARS. Conclusion: This study concludes the Paeonia emodi Royle as a potential drug which relieves the pain and immune-mediated arthritis by downregulating pro-inflammatory cytokines as well as by modulating the oxidative storm.